To circ or not to circ: clinical and pharmacoeconomic outcomes of a prospective trial of topical steroid versus primary circumcision - Nobre, Yuri D. [UNIFESP] (2010)
PURPOSE: To compare the efficacy and costs of circumcision versus topical treatment using a prospective pharmacoeconomic protocol. MATERIALS AND METHODS: We treated 59 patients (3-10 years of age) randomized into two groups: 29 underwent an 8-week course of topical treatment with 0.2% betamethasone-hyaluronidase cream twice a day; and 30 underwent circumcision. Topical treatment success was defined as complete exposure of the glans. In cases of treatment failure, circumcision was performed and its cost imputed to that of the initial treatment. The pharmacoeconomic aspects were defined according to the Brazilian National Public Health System database and the Brazilian Community Pharmacies Index. RESULTS: The two groups were statistically similar for all clinical parameters evaluated. Topical treatment resulted in complete exposure of the glans in 52% of the patients. Topical treatment was associated with preputial pain and hyperemia. However, treatment suspension was unnecessary. Minor complications were observed in 16.6% of the surgical group patients. The mean cost per patient was US$ 53.70 and US$ 125.20, respectively, for topical steroid treatment (including the costs related to treatment failure) and circumcision. The total costs were US$ 2,825.32 and US$ 3,885.73 for topical treatment and circumcision, respectively. CONCLUSIONS: Topical treatment of phimosis can reduce costs by 27.3% in comparison with circumcision. Therefore, topical treatment of phimosis should be considered prior to the decision to perform surgery.